A Farm Business Model for aquaculture centric farming system - Ponnusamy, K (Indian Farming, 2016)
Documenting the successful journey of a farmer turning asentrepreneur helps the researchers to generate researchable issues, the planners and extension workers to design strategies and also fellow farmers to learn and adopt the innovative approaches to profitable farming. The case study of businessmodel of the farmer revealed that an ideal enterprise combination selected on the basis of the availability oflocal resources, situations, opportunities and problems wouldlead to enhanced income and employment generation at farm level apart from providing food and nutritional security for family and input recycling at farm level. Identification and adoption ofdifferent enterprises which yield regular returns on investment without any constraints on land or human resources is essential. The extension agencies need to propagate the technologies for the farming system rather than focusing on individual farm enterprises. The government must bring out suitable policymeasures for implementing this concept under broad-based extension system.